Adolescent genitourinary anomalies: managing transition. Issue 1 (26th January 2021) - Woodhouse, Christopher
Abstract : Parents have limited aspirations for children with major congenital anomalies and have difficulty in preparing themselves for their maturity. Many general lessons can be learnt from experience in urology and vice versa .